Effect of superheated steam treatment on the mechanical properties and dimensional stability of PALF/PLA biocomposite - Challabi, Ahmed Jaafar Hussein; Chieng, Buong Woei; Ibrahim, Nor Azowa; Ariffin, Hidayah; Zainuddin, Norhazlin (MDPI, 2019)
The effectiveness of superheated steam (SHS) as an alternative, eco-friendly treatment method to modify the surface of pineapple leaf fiber (PALF) for biocomposite applications was investigated. The aim of this treatment was to improve the interfacial adhesion between the fiber and the polymer. The treatment was carried out in an SHS oven for different temperatures (190–230 °C) and times (30–120 min). Biocomposites fabricated from SHS-treated PALFs and polylactic acid (PLA) at a weight ratio of 30:70 were prepared via melt-blending techniques. The mechanical properties, dimensional stability, scanning electron microscopy (SEM), and X-ray diffraction (XRD) for the biocomposites were evaluated. Results showed that treatment at temperature of 220 °C for 60 min gave the optimum tensile properties compared to other treatment temperatures. The tensile, flexural, and impact properties as well as the dimensional stability of the biocomposites were enhanced by the presence of SHS-treated PALF. The SEM analysis showed improvement in the interfacial adhesion between PLA and SHS-treated PALF. XRD analysis showed an increase in the crystallinity with the addition of SHS-PALF. The results suggest that SHS can be used as an environmentally friendly treatment method for the modification of PALF in biocomposite production.